An international multicentre observational cohort study of the clinical presentation of acute arboviral infection (ARIA): a study protocol - Josephine Bourner; Giselle Duarte; Leonardo S. L. Bastos; Timo Tolppa; Janice Caoili; Madiha Hashmi; Jose Cerbino-Neto; Priscilla Soares Filgueiras; Arishay Hussaini; Elise Pesonel; John Amuasi; Joseph Bonney; et al. (BMC Infectious Diseases, 2026)
Abstract Background Despite the growing global burden of diseases caused by arboviruses, there remain substantial gaps in our understanding of the clinical presentation and natural history of arboviral infections, especially in the acute phase. There is a critical need for robust, multicentre, and internationally harmonised data to characterise the clinical features of arboviral infections, identify early predictors of severe disease, and inform the development of diagnostic algorithms, case definitions and research study design. This study aims to address these gaps by establishing an international multicentre observational cohort focused on the clinical presentation and evolution of acute arboviral infections. Methods The study will be conducted across primary, secondary, and tertiary healthcare settings in multiple countries. Participating countries have the flexibility to implement the protocol at any level of their health system, depending on local context and infrastructure, and adapt the protocol according to local research interests. The protocol uses a tiered approach to sample and data collection to support implementation according to site capacity. Tier 1 is the core protocol described in this article and sites can define additional data (Tier 2) and sample (Tier 3) collection according to local resource capacity and research interest. The study will enrol patients with clinically suspected or confirmed arboviral infection who present to a participating healthcare facility within seven days of symptom onset. Participants will be enrolled for a maximum of 10 days, during which data on signs and symptoms, interventions, routine laboratory results will be collected daily. Outcome information will be collected on D10. Discussion The systematic collection of comparable, and contextually-adaptable data on arboviral illnesses aims to generate a harmonised data set of global presentations of acute arbovirus infection and map the patient journey through their illness. The resulting dataset aims to provide evidence to support improvements in patient management, feasible research study design, and accelerate the development of diagnostic and therapeutic interventions. Ultimately, this collaborative effort aims to contribute towards a coordinated global response to arboviral diseases. Clinical trial number Not applicable.